2005
DOI: 10.1099/mic.0.28036-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered morphology produced by ftsZ expression in Corynebacterium glutamicum ATCC 13869

Abstract: Corynebacterium glutamicum is a Gram-positive bacterium that lacks the cell division FtsA protein and actin-like MreB proteins responsible for determining cylindrical cell shape. When the cell division ftsZ gene from C. glutamicum (ftsZ Cg ) was cloned in different multicopy plasmids, the resulting constructions could not be introduced into C. glutamicum; it was assumed that elevated levels of FtsZ Cg result in lethality. The presence of a truncated ftsZ Cg and a complete ftsZ Cg under the control of Plac led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Nucleoid occlusion is not seen in S. coelicolor and C. glutamicum during divisome assembly (164,333,369). Using fluorescence microscopy, the images seem to show overlapping nucleoid staining and FtsZ-green fluorescent protein (GFP) fluorescence; however, it could be that the resolution of such imaging is unable to detect the initiation of chromosome partitioning that may have already begun in the bacteria.…”
Section: What Are the Negative Regulators Of Ftsz Assembly?mentioning
confidence: 97%
See 1 more Smart Citation
“…Nucleoid occlusion is not seen in S. coelicolor and C. glutamicum during divisome assembly (164,333,369). Using fluorescence microscopy, the images seem to show overlapping nucleoid staining and FtsZ-green fluorescent protein (GFP) fluorescence; however, it could be that the resolution of such imaging is unable to detect the initiation of chromosome partitioning that may have already begun in the bacteria.…”
Section: What Are the Negative Regulators Of Ftsz Assembly?mentioning
confidence: 97%
“…A 4-fold decrease in FtsZ was found to result in aberrant cells with buds, branches, and knots, but no filaments, while a 20-fold decrease yielded large, club-shaped cells (333). Promoter analysis of the M. tuberculosis ftsZ allele revealed up to six promoters, indicating a high level of transcriptional regulation available as well as the possible need for elevated basal levels of FtsZ in mycobacteria (355).…”
Section: What Is Missing In Actinomycetes?mentioning
confidence: 99%
“…Membrane staining has indicated that certain lipid domains might be enriched at division sites, either as a cause or an effect of Z-ring localization 60 . Alternative factors in ring positioning will probably be important in the many species that lack the Min system, or in species that do not exhibit obvious nucleoid occlusion 61,62 .…”
Section: Spatial Regulationmentioning
confidence: 99%
“…The P gntK promoter is located upstream of the gntK gene encoding the C. glutamicum gluconate kinase and is regulated by sucrose (2). The E. coli P lac promoter allows low expression levels in C. glutamicum (52). In C. glutamicum, pKLA/B and pKPKA/B were unable to replicate autonomously but integrated by homologous recombination into the chromosomal pknA/B locus, respectively.…”
Section: Activation Of Pkng Phosphorylation Is Dependent On Amentioning
confidence: 99%